(untitled) (Cadernos de Sociomuseologia, 2017)
In May 2003, the National Museum Policy was launched in Brazil, by the initiative of the Ministry of Culture, led by Minister Gilberto Gil, during the first government of President Luiz Inácio Lula da Silva.